IS DEBT TO EQUITY RATIO, CURRENT RATIO, AND RETURN ON ASSETS ON MARKET RESPONSE AS FORMING OF FIRM VALUE? - Sabarudin Muslim; Yudhi Herliansyah; Meifida Ilyas (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze whether the balance of company value measured by PBV is determined by the Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach, data was collected from the financial statements of listed companies during the period 2021-2023. The results show that DER and CR are not determinants of PBV, meaning that the share price formed in the market as the equilibrium value of the company is not determined by the size of the capital structure and the company's ability to pay debts, but only by ROA or the company's ability to earn profits or the company's ability to use its assets to generate profits. The greater the company's ability to generate returns in the form of profits on the assets utilized by the company, the more investors view it as a good operation, thereby increasing investor interest in companies that demonstrate a high balance of firm value.